The dietary inflammatory index and cardiometabolic parameters in US firefighters - Christodoulou, Andria; Christophi, Costas A.; Sotos-Prieto, Mercedes; Moffatt, Steven M.; Zhao, Longgang; Kales, Stefanos N.; Hébert, James R. (My University, 2024)
Dietary choices play a crucial role in influencing systemic inflammation and the eventual development of cardiovascular diseases (CVD). The Dietary Inflammatory Index (DII®) is a novel tool designed to assess the inflammatory potential of one's diet. Firefighting, which is characterized by high-stress environments and elevated CVD risk, represents an interesting context for exploring the dietary inflammatory-CVD connection.
Keywords: inflammatory index; DII scores; US firefighters; cardiovascular disease; nutrition